Peak oxygen uptake in older adults with heart failure: a systematic review and meta-analysis - Veronika Schmid; Sarah Paterson; Christopher Weinkauf; Jing Wang; Corey R. Tomczak; David Niederseer; Jan Vontobel; Daniel E. Forman; Martin Halle; Michael D. Nelson; Stephen J. Foulkes; Mark J. Haykowsky (GeroScience, 2025)

Quantifying land surface changes to climatic and anthropogenic forcings by analyses of a time-series of remotely sensed images from 1936 to 2021 for a former dust bowl drought area in western Kansas, USA - Sowmya Revanna; Steven L. Forman; Liliana C. Marin; Andrew J. Hamara (Remote Sensing Applications: Society and Environment, 2025)

Sex differences in the association between skeletal muscle energetics and perceived physical fatigability: the Study of Muscle, Mobility and Aging (SOMMA) - Emma L. Gay; Paul M. Coen; Stephanie Harrison; Reagan E. Garcia; Yujia Qiao; Bret H. Goodpaster; Daniel E. Forman; Frederico G. S. Toledo; Giovanna Distefano; Philip A. Kramer; Sofhia V. Ramos; Anthony J. A. Molina; et al. (GeroScience, 2024)

Chronology and evolution of the world's largest sand island: K'gari (Fraser Island), South East Queensland, Australia - J. Shulmeister; T.M. Rittenour; N.R. Patton; D. Ellerton; A. Gontz; P.A. Hesp; T. Santini; G. Miot da Silva; S. Forman; H. Bowyer; J.T. Kelly; A. McCallum; et al. (Quaternary Science Reviews, 2024)

Where did the water come from? Wetlands and shallow lakes in semi‐arid dunefields from South America during the Pleistocene–Holocene transition - Alfonsina Tripaldi; Ivana L. Ozán; Guillermo Heider; María J. Orgeira; Steven L. Forman (Journal of Quaternary Science, 2024)
Stabilized and active dunes and sand sheet deposits abound in a small lake‐dotted semi‐arid region of the Western Pampean Dunefield, Argentina. Here, a multi‐scale and multi‐proxy study of three sites, across a hydrologic gradient from lakes to a dryland with groundwater levels at more than 25 m depth, analyzes calcareous and ferruginous rhizoliths, calcareous crusts, hypocoatings, pedogenic carbonate and amorphous Mn‐oxide precipitates within blowout dunes. These palustrine‐related features indicate significantly wetter conditions that allowed the development of shallow lakes and expanding wetlands during the Pleistocene–Holocene transition, limited by associated optically stimulated luminescence ages between ca. 14.7 and 11.6 ka. These wetter conditions, also identified in other nearby proxy records, may be associated with a strengthened South American Monsoon System, potentially during the Younger Dryas Chronozone, though other geological, ecological and climatic forcings cannot be ruled out with available data. Such a scenario lacks a modern analogue, since current hydrologic excess, evidenced in the formation of lakes and new rivers, is not observed in the localities which record paleolakes. This study underlines the variable conditions for pronounced hydrologic excess in semi‐arid eolian environments in western Argentina with complex ecological, anthropogenic and climatic linkages.

Lower muscle mitochondrial energetics is associated with greater phenotypic frailty in older women and men: the Study of Muscle, Mobility and Aging - Theresa Mau; Haley N. Barnes; Terri L. Blackwell; Philip A. Kramer; Scott R. Bauer; David J. Marcinek; Sofhia V. Ramos; Daniel E. Forman; Frederico G. S. Toledo; Russell T. Hepple; Stephen B. Kritchevsky; Steven R. Cummings; et al. (GeroScience, 2023)

The role of self-compassion and its individual components in adaptive responses to dietary lapses - Charlotte J. Hagerman; Marny M. Ehmann; Lauren C. Taylor; Evan M. Forman (Appetite, 2023)

Active thrust tectonics along the western slope of the Central Andes southernmost Pampean flat-slab segment (∼33°S, Chile): The Cariño Botado fault system - J. Estay; L. Pinto; G. Easton; G.P. De Pascale; M. Troncoso; S. Carretier; S.L. Forman (Geomorphology, 2023)

Human Lumbar Spine Injury Risk in Dynamic Combined Compression and Flexion Loading - Sophia K. Tushak; Bronislaw D. Gepner; Jason L. Forman; Jason J. Hallman; Bengt Pipkorn; Jason R. Kerrigan (Annals of Biomedical Engineering, 2023)

Quantifying the Effect of Sex and Neuroanatomical Biomechanical Features on Brain Deformation Response in Finite Element Brain Models - Kristen A. Reynier; J. Sebastian Giudice; Pavel Chernyavskiy; Jason L. Forman; Matthew B. Panzer (Annals of Biomedical Engineering, 2022)

Ruminative reflection is associated with anticorrelations between the orbitofrontal cortex and the default mode network in depression: implications for repetitive transcranial magnetic stimulation - Tobin J. Ehrlich; Jyoti Bhat; Andrea M. Horwege; Daniel H. Mathalon; Gary H. Glover; Brian J. Roach; Bashar W. Badran; Steven D. Forman; Mark S. George; J. Cobb Scott; Michael E. Thase; Jerome A. Yesavage; et al. (Brain Imaging and Behavior, 2022)
Patients with depression who ruminate repeatedly focus on depressive thoughts; however, there are two cognitive subtypes of rumination, reflection and brooding, each associated with different prognoses. Reflection involves problem-solving and is associated with positive outcomes, whereas brooding involves passive, negative, comparison with other people and is associated with poor outcomes. Rumination has also been related to atypical functional hyperconnectivity between the default mode network and subgenual prefrontal cortex. Repetitive pulse transcranial magnetic stimulation of the prefrontal cortex has been shown to alter functional connectivity, suggesting that the abnormal connectivity associated with rumination could potentially be altered. This study examined potential repetitive pulse transcranial magnetic stimulation prefrontal cortical targets that could modulate one or both of these rumination subtypes. Forty-three patients who took part in a trial of repetitive pulse transcranial magnetic stimulation completed the Rumination Response Scale questionnaire and resting-state functional magnetic resonance imaging. Seed to voxel functional connectivity analyses identified an anticorrelation between the left lateral orbitofrontal cortex (−44, 26, −8; k = 172) with the default mode network-subgenual region in relation to higher levels of reflection. Parallel analyses were not significant for brooding or the RRS total score. These findings extend previous studies of rumination and identify a potential mechanistic model for symptom-based neuromodulation of rumination.

Investigating the importance of B cells and antibodies during Trichuris muris infection using the IgMi mouse - Rinal Sahputra; Emma A Murphy; Ruth Forman; Iris Mair; Muhammad Z. H. Fadlullah; Ari Waisman; Werner Muller; Kathryn J. Else (Journal of Molecular Medicine, 2020)
The IgMi mouse has normal B cell development; its B cells express an IgM B cell receptor but cannot class switch or secrete antibody. Thus, the IgMi mouse offers a model system by which to dissect out antibody-dependent and antibody-independent B cell function. Here, we provide the first detailed characterisation of the IgMi mouse post- Trichuris muris ( T. muris ) infection, describing expulsion phenotype, cytokine production, gut pathology and changes in T regulatory cells, T follicular helper cells and germinal centre B cells, in addition to RNA sequencing (RNA seq) analyses of wild-type littermates (WT) and mutant B cells prior to and post infection. IgMi mice were susceptible to a high-dose infection, with reduced Th2 cytokines and elevated B cell-derived IL-10 in mesenteric lymph nodes (MLN) compared to controls. A low-dose infection regime revealed IgMi mice to have significantly more apoptotic cells in the gut compared to WT mice, but no change in intestinal inflammation. IL-10 levels were again elevated. Collectively, this study showcases the potential of the IgMi mouse as a tool for understanding B cell biology and suggests that the B cell plays both antibody-dependent and antibody-independent roles post high- and low-dose T. muris infection. Key messages During a high-dose T. muris infection, B cells are important in maintaining the Th1/Th2 balance in the MLN through an antibody-independent mechanism. High levels of IL-10 in the MLN early post-infection, and the presence of IL-10-producing B cells, correlates with susceptibility to T. muris infection. B cells maintain gut homeostasis during chronic T. muris infection via an antibody-dependent mechanism.

Demonstrating Contribution of Components of Fixed-Dose Drug Combinations Through Longitudinal Exposure-Response Analysis - Asbjørn Nøhr-Nielsen; Theis Lange; Julie Lyng Forman; Theodoros Papathanasiou; David J. R. Foster; Richard N. Upton; Ole Jannik Bjerrum; Trine Meldgaard Lund (The AAPS Journal, 2020)

SVCT2 Expression and Function in Reactive Astrocytes Is a Common Event in Different Brain Pathologies - Katterine Salazar; Fernando Martínez; Margarita Pérez-Martín; Manuel Cifuentes; Laura Trigueros; Luciano Ferrada; Francisca Espinoza; Natalia Saldivia; Romina Bertinat; Katherine Forman; María José Oviedo; Antonio J. López-Gambero; et al. (Molecular Neurobiology, 2018)

The Oxygen Paradox, the French Paradox, and age-related diseases - Joanna M. S. Davies; Josiane Cillard; Bertrand Friguet; Enrique Cadenas; Jean Cadet; Rachael Cayce; Andrew Fishmann; David Liao; Anne-Laure Bulteau; Frédéric Derbré; Amélie Rébillard; Steven Burstein; et al. (GeroScience, 2017)

Canine genome assembly correction facilitates identification of a MAP9 deletion as a potential age of onset modifier for RPGRIP1-associated canine retinal degeneration - Oliver P. Forman; Rebekkah J. Hitti; Mike Boursnell; Keiko Miyadera; David Sargan; Cathryn Mellersh (Mammalian Genome, 2016)

Diets of deepwater oreos (Oreosomatidae) and orange roughy Hoplostethus atlanticus - J. S. Forman; P. L. Horn; D. W. Stevens (Journal of Fish Biology, 2016)
The diets of black oreo Allocyttus niger , smooth oreo Pseudocyttus maculatus , spiky oreo Neocyttus rhomboidalis and orange roughy Hoplostethus atlanticus were determined from examination of contents of 240, 311, 76 and 415 non‐empty stomachs, from fishes sampled by bottom trawl on Chatham Rise to the east of South Island, New Zealand. Hoplostethus atlanticus had an opportunistic predatory strategy with a broad diet dominated by prawns and mesopelagic teleosts, but with substantial components of mysids and cephalopods. Pseudocyttus maculatus was strongly specialized on gelatinous zooplankton (jellyfish and salps). Allocyttus niger consumed mainly salps and hyperiid amphipods, and to a lesser extent fishes, prawns, mysids and copepods. Neocyttus rhomboidalis primarily consumed salps, along with mysids, euphausiids and fishes. Only P. maculatus did not exhibit significant ontogenetic variation in diet. The diets were also influenced by year and bottom depth. Differences in the distributions and diets of the four species probably reduce conflicts in resource use.

Consenting postpartum women for use of routinely collected biospecimens and/or future biospecimen collection - Claudia A. Kozinetz; Kathryn Royse; Sarah C. Graham; Xiaoying Yu; Jack Moye; Beatrice J. Selwyn; Michele R. Forman; Chantal Caviness (Journal of Community Genetics, 2016)

Last interglacial vegetation and climate history from the Portuguese coast - T. A. MINCKLEY; J. A. HAWS; M. M. BENEDETTI; S. C. BREWER; S. L. FORMAN (Journal of Quaternary Science, 2015)
We examine the Atlantic maritime vegetation history from Praia Rei Cortiço, Portugal, to understand natural vegetation patterns and infer climatic conditions during the transition from the last interglacial to early glacial periods. Optically stimulated luminescence dating of quartz grains from sediments surrounding the 1.3‐m‐thick organic deposit date the section to within 120–89 ka. Pollen data were used to reconstruct the vegetation history and determine a range of possible past climates using an ensemble of seven modern analogue approaches. A five‐part environmental sequence transitioned from heath‐pine‐dominated communities, deciduous hardwood forests and pine forests to heathlands surrounded by steppe‐like environments. Mixed temperate and Mediterranean forest elements existed during the last interglacial period at Praia Rei Cortiço, suggesting a proximal limit to these floras. Abundant Fagus pollen (>6%) suggests local beech populations existed within maritime forests of the Iberian Atlantic margin, representing a greater distribution of this genus during interglacial periods than has previously been recognized. Climate reconstructions indicate that variations in moisture availability may have been a major driver of the observed environmental changes.

Silver spoons in the rough: can environmental enrichment improve survival of hatchery Atlantic salmon Salmo salar in the wild? - L. J. Roberts; J. Taylor; P. J. Gough; D. W. Forman; C. Garcia de Leaniz (Journal of Fish Biology, 2014)
This study tested the ‘silver spoon’ hypothesis which posits that individuals that develop under favourable conditions should enjoy a fitness advantage later in life because they are more likely to recognize and settle in high‐quality habitats. Atlantic salmon Salmo salar of two age classes (0+ and 1+ years) were reared in environmentally enriched or standard hatchery tanks for a short period ( c. 10 weeks), were then released into a natural river and sampled on repeated occasions to test for silver‐spoon effects. Compared with controls, enriched fish had a 6·4% higher recapture rate and settled in higher velocity habitats when they were stocked as 0+ year fry, but not when they were stocked as 1+ year parr. The opportunity for selection was generally higher for environmentally enriched fish than for controls, and also higher for 0+ than for 1+ year fish. Selection favoured individuals with high condition factor, extensive fat reserves and longer than average pectoral fins in both age classes but favoured a small body size in 1+ year and a large body size in 0+ year releases. Stomach analysis showed that enriched fish ate more, and adapted quicker to natural prey than controls. These results provide support for silver‐spoon effects in fish and indicate that enrichment can improve post‐release performance in conservation programmes, but seemingly only if fish are not kept in captivity for too long.

Connecting Satellite Observations with Water Cycle Variables Through Land Data Assimilation: Examples Using the NASA GEOS-5 LDAS - Rolf H. Reichle; Gabriëlle J. M. De Lannoy; Barton A. Forman; Clara S. Draper; Qing Liu (Surveys in Geophysics, 2014)

Moon phase influences the diet of southern Ray's bream Brama australis - P. L. Horn; J. S. Forman; M. R. Dunn (Journal of Fish Biology, 2013)
Diet composition of the southern Ray's bream Brama australis was examined from stomach contents of 399 specimens sampled by bottom trawl on Chatham Rise to the east of South Island, New Zealand, over 3 years. Prey items were predominantly mesopelagic fishes and crustaceans. Multivariate analysis indicated that moon phase explained more of the diet variability than any other predictor examined. It appears likely that diet composition is influenced by a combination of changes in both tidal flows and illumination. Different combinations of prey were consumed by B. australis at different times of the lunar cycle. An influence of moon phase on feeding by fishes has rarely been reported, but it is likely that moon phase influences the diets of other species that specialize in mesopelagic prey. The most important prey group by mass for B. australis was Myctophidae (primarily Lampanyctodes hectoris ), followed by Stomiiformes (primarily Maurolicus australis ) and shrimps ( Sergestes spp). An ontogenetic shift in diet was observed, from numerical dominance by small crustaceans including amphipods and euphausiids (with some fishes) in smaller (mass B. australis to pelagic teleost prey (with a few larger crustaceans) in larger (>1440 g) B. australis .

Diet and trophic niche of Antarctic silverfish Pleuragramma antarcticum in the Ross Sea, Antarctica - M. H. Pinkerton; J. Forman; S. J. Bury; J. Brown; P. Horn; R. L. O'Driscoll (Journal of Fish Biology, 2013)
The diet of Antarctic silverfish Pleuragramma antarcticum was evaluated by examining stomach contents of specimens collected in the Ross Sea (71°–77° S; 165°–180° E) in January to March 2008. Pleuragramma antarcticum (50–236 mm standard length, L S ) and prey items were analysed for stable‐isotopic composition of carbon and nitrogen. According to index of relative importance ( I RI ), which incorporates frequency of occurrence, mass and number of prey items, the most important prey items were copepods (81% I RI over all specimens), predominantly Metridia gerlachei and Paraeuchaeta sp., with krill and fishes having low I RI (2·2 and 5·6% I RI overall). According to mass of prey ( M ) in stomachs, however, fishes ( P. antarcticum and myctophids) and krill dominated overall diet (48 and 22% M , respectively), with copepods being a relatively minor constituent of overall diet by mass (9·9% M ). Piscivory by P. antarcticum occurred mainly in the extreme south‐west of the region and near the continental slope. Krill identified to species level in P. antarcticum stomachs were predominantly Euphausia superba (14·1% M ) with some Euphausia crystallophorias (4·8% M ). Both DistLM modelling (PRIMER‐permanova+) on stomach contents (by I RI ) and stepwise generalized linear modelling on stable isotopes showed that L S and location were significant predictors of P. antarcticum diet. Postlarval P. antarcticum (50–89 mm L S ) consumed exclusively copepods. Juvenile P. antarcticum (90–151 mm L S ) consumed predominantly krill and copepods by mass (46 and 30% M , respectively). Small adult P. antarcticum (152–178 mm L S ) consumed krill, fishes and copepods (37, 36 and 15% M , respectively). Large adult P. antarcticum (179–236 mm L S ) consumed predominantly fishes and krill (55 and 17% M , respectively), especially in the north (near the Ross Sea slope) and in the SW Ross Sea. Amphipods were occasionally important prey items for P. antarcticum (western Ross Sea, 39% M ). General concordance between stomach contents and trophic level of P. antarcticum and prey based on δ 15 N was demonstrated. Pleuragramma antarcticum trophic level was estimated as 3·7 (postlarval fish) and 4·1 (fish aged 3+ years).

Diet and scavenging habits of the smooth skate Dipturus innominatus - J. S. Forman; M. R. Dunn (Journal of Fish Biology, 2012)
The diet of smooth skate Dipturus innominatus was determined from examination of stomach contents of 321 specimens of 29·3–152·0 cm pelvic length, sampled from research and commercial trawlers at depths of 231–789 m on Chatham Rise, New Zealand. The diet was dominated by the benthic decapods Metanephrops challengeri and Munida gracilis , the natant decapod Campylonotus rathbunae and fishes from 17 families, of which hoki Macruronus novaezelandiae , sea perch Helicolenus barathri , various Macrouridae and a variety of discarded fishes were the most important. Multivariate analyses indicated the best predictors of diet variability were D. innominatus length and a spatial model. The diet of small D. innominatus was predominantly small crustaceans, with larger crustaceans, fishes and then scavenged discarded fishes increasing in importance as D. innominatus got larger. Scavenged discards were obvious as fish heads or tails only, or skeletal remains after filleting, often from pelagic species. Demersal fish prey were most frequent on the south and west Chatham Rise, in areas where commercial fishing was most active. Dipturus innominatus are highly vulnerable to overfishing, but discarding practices by commercial fishing vessels may provide a positive feedback to populations through improved scavenging opportunities.

Diet and dietary variation of New Zealand hoki Macruronus novaezelandiae - AM Connell; MR Dunn; J Forman (New Zealand Journal of Marine and Freshwater Research, 2010)
The diet of hoki was determined from examination of stomach contents of 1992 fish of 26–112 cm total length (TL) sampled at depths of 209–904m on Chatham Rise, New Zealand, from summer research trawl surveys and seasonal commercial fishing trawls, during 2004–2008. Prey was predominantly euphausiids, mesopelagic fishes and natant decapods. Multivariate analyses using distance‐based linear models, non‐parametric multi‐dimensional scaling and similarity percentages indicated that the best predictors of diet variability were the position of the fish in relation to the subtropical front (STF), fish size and longitude. Pasiphaeids were more important to the north of the STF, and sternoptychid fishes and euphausiids more important in the STF convergence area. Euphausiids and sternoptychid fishes were important for smaller hoki (26–55 cm TL), myctophid fishes and natant decapods for larger hoki, and macrourids for the largest hoki (>84 cm TL). The longitudinal effect was characterised by pasiphaeids, euphausiids and sternoptychids to the west, and myctophids in the centre of Chatham Rise. Feeding activity was analysed using generalised additive models, and was found to vary with time of day, sample source (research or commercial), longitude, hoki size and depth. The variability in diet suggested hoki forage opportunistically within their preferred habitat and biological limits.

Cardiological aging in SAM model: effect of chronic treatment with growth hormone - K. Forman; E. Vara; C. García; C. Ariznavarreta; G. Escames; J. A. F. Tresguerres (Biogerontology, 2010)

Feeding habits of alfonsino Beryx splendens - P. L. Horn; J. Forman; M. R. Dunn (Journal of Fish Biology, 2010)
The diet of the alfonsino Beryx splendens was determined from examination of stomach contents of 287 specimens of 17 to 48 cm fork length ( L F ) sampled by bottom trawl on the Chatham Rise to the east of New Zealand. Prey items were predominantly crustaceans and mesopelagic fishes. The most important prey species by mass was Sergestes spp. prawns, followed by the myctophid Lampanyctodes hectoris , and then Pasiphaea spp. prawns. Multivariate analyses indicated that small crustaceans (euphausiids and amphipods) were most important in the diet of smaller B. splendens (100–424 g, 17–26·5 cm), with larger prawn species and mesopelagic fishes most important for larger fish (425–2070 g, 27–46 cm). Moon phase and bottom temperature also explained some of the variability in diet, but the moon phase effect was difficult to explain, and the bottom temperature effect may have been confounded, to some extent, with L F . The results indicated that B. splendens were moderately selective feeders that foraged primarily in the mesopelagic layers. The diet of New Zealand B. splendens is generally similar to those reported from other areas, i.e. dominated by mesopelagic crustaceans and fishes, and with a transition from small crustaceans to fishes with increasing predator size.

Night stocking facilitates nocturnal migration of hatchery‐reared Atlantic salmon, Salmo salar , smolts - L. J. ROBERTS; J. TAYLOR; P. J. GOUGH; D. W. FORMAN; C. GARCIA De LEANIZ (Fisheries Management and Ecology, 2009)
Hatchery‐reared salmon, Salmo salar L., smolts are generally stocked during daylight hours, but the natural migration of smolts tends to occur at night. Recapture rates and timing of migration were compared between Atlantic salmon smolts stocked during the day and during the evening. Timing of release had no significant effect on the number of smolts recaptured, but had a strong effect on nocturnal behaviour. When stocked in the evening (but not during the day) hatchery‐reared smolts moved almost exclusively during the night. This study suggests that timing the release to coincide with the natural time of smolt migration may provide valuable acclimatisation and facilitate nocturnal smolt passage.

A novel technique for isolating functional mast cells from the heart - L. G. Morgan; S. P. Levick; T. G. Voloshenyuk; D. B. Murray; M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2008)

Rat cardiac mast cell maturation and differentiation following acute ventricular volume overload - M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2006)

Spontaneous histamine secretion during isolation of rat cardiac mast cells - M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2004)

Serum tocopherols, selenium and lung cancer risk among tin miners in China - Duminda Ratnasinghe; Joseph A. Tangrea; Michele R. Forman; Terry Hartman; Elaine W. Gunter; You-Lin Qiao; Shu-Xiang Yao; Michael J. Barett; Carol A. Giffen; Yener Erozan; Melvyn S. Tockman; Philip R. Taylor (Cancer Causes & Control, 2000)

The immunological response of pigs and Guinea pigs to antigens of African swine fever virus - A. J. Forman; R. C. Wardley; P. J. Wilkinson (Archives of Virology, 1982)